Medium-term results of the HINTEGRA total ankle arthroplasty - Khademi, Mohammadali; Ferrao, Paulo; Saragas, Nikiforos (Journal of the Foot & Ankle, 2020)
Objective: The aim of this study was to determine patient satisfaction, survivorship, and revision rate of the HINTEGRA total ankle arthroplasty (TAA). Our secondary objective was to assess hindfoot function. Methods: All patients who underwent a HINTEGRA TAA between 2007 and 2014 were evaluated. We included a total of 69 patients (69 ankles), who were subjected to clinical and radiological examination and completed a visual analogue scale (VAS) for pain, the American Orthopaedic Foot and Ankle Society (AOFAS) ankle score, and the self-reported foot and ankle score (SEFAS). Hindfoot function was assessed using the AOFAS hindfoot score. Mean follow-up was 62 (57–101) months. Results: The mean VAS score was 2 (0–3) and the SEFAS was 37 (26–48) at the most recent follow-up, while the AOFAS ankle score improved from 57 (52–62) to 87 (82–93). The AOFAS hindfoot score improved from 82 to 92 postoperatively. Eight patients had periprosthetic osteolysis and 5 underwent bone grafting of cysts. We detected polyethylene and hydroxyapatite particles in specimens obtained from the cysts. Eight patients had their procedures converted to an ankle arthrodesis. Conclusion: In select patients, TAA improved quality of life. Our medium-term follow-up of the HINTEGRA TAA observed a survivorship of 89% at 5 years with an improvement in the AOFAS score and a mean SEFAS score of 37. We recommend that large periprosthetic cysts, which may be caused by the hydroxyapatite coating and polyethylene particles, be bone grafted prophylactically. We found hindfoot function to be preserved. Level of Evidence IV; Therapeutic Studies; Case Series.